The Role of Employee Engagement in Mediating the Effect of Turnover Intention and Quality of Work Life on Employee Performance at BPR Padma, Sesetan Head Office - TEMAJA, I Made Dwi Jaya; SARA , I Made (Journal of Tourism Economics and Policy, 2025)
Employee performance must be considered to ensure that each employee carries out their functions effectively and efficiently. BPR Padma Sesetan Head Office faces challenges in human resource management which are specifically viewed from the aspect of employee welfare. The high level of employee turnover intention at BPR Padma Sesetan Head Office is also accompanied by a fairly low level of quality of work life which is a problem that can have an impact on overall employee performance. This research aims to determine the influence of turnover intention and quality of work life on employee performance directly or through the mediating role of employee engagement. The population in this study were all employees at BPR Padma Sesetan Head Office. The sample taken was 56 respondents with saturated sampling method. Data collection methods are questionnaires, observation, and literature study. The analysis technique used Partial Least Square (PLS) based on Structural Equation Modeling (SEM). The results of the study found that turnover intention has a negative and significant effect on employee performance, quality of work life has a positive and significant effect on employee performance, turnover intention has a negative and insignificant effect on employee engagement, quality of work life has a positive and significant effect on employee engagement, employee engagement has a positive and significant effect on employee performance, employee engagement is not able to mediate the effect of turnover intention on employee performance, and employee engagement is not able to mediate the effect of quality of work life on employee performance.